2020
DOI: 10.1007/s10286-020-00729-7
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in post-traumatic stress disorder risk: autonomic control and inflammation

Abstract: Aim: Over 7 million U.S. adults and about 20% of the military population have post-traumatic stress disorder (PTSD), a debilitating condition that is independently linked to a significantly greater risk of developing cardiovascular disease (CVD). Women have twice the probability of developing PTSD after experiencing a traumatic event compared to men. Existing literatures have reported higher inflammation and autonomic dysfunction including impaired baroreflex sensitivity, increased sympathetic reactivity and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 101 publications
2
19
0
Order By: Relevance
“…All COVID-19-related manuscripts are Open Access immediately upon publication. We also published a special issue on sex differences in cardiovascular autonomic control [ 1 , 3 , 4 , 8 , 9 , 11 ]. The reception of these series was exceptionally good.…”
mentioning
confidence: 99%
“…All COVID-19-related manuscripts are Open Access immediately upon publication. We also published a special issue on sex differences in cardiovascular autonomic control [ 1 , 3 , 4 , 8 , 9 , 11 ]. The reception of these series was exceptionally good.…”
mentioning
confidence: 99%
“…160,173 Sex differences in the relationship between inflammation and human behavior are substantive enough that many researchers are now urging the field to explicitly evaluate sex as a biological variable in future research. 157,158,160,168,174 Data explicitly examining the role of sex in the relationship between inflammation, neurocircuitry, and the three RDoC components examined in this article (reward processing, motor processing, and threat reactivity) are currently sparse, but a few preliminary observations can be posited. First, sex differences may influence the relationship between reward processing and inflammation that are mediated by corticostriatal circuitry.…”
Section: Sex Differences In the Effects Of Inflammation On Behaviormentioning
confidence: 99%
“…Several reports link PTSD with increased inflammation and occurrence of inflammatory disorders (16)(17)(18)(19)(20)(21)(22)(23)(24)(25). In an early report by Gola et al, researchers found that peripheral blood mononuclear cells (PBMCs) from PTSD patients exhibited a more pre-activated phenotype, having higher levels of secreting inflammatory cytokines, such as interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-a), and IL-1b when compared to control samples (26).…”
Section: Introductionmentioning
confidence: 99%